Characteristics and Therapeutic Potential of Dental Pulp Stem Cells on Neurodegenerative Diseases - Ueda, Tomoyuki; Inden, Masatoshi; Ito, Taisei; Kurita, Hisaka; Hozumi, Isao (Frontiers in Neuroscience, 2020)
To evaluate the therapeutic potential of stem cell for neurodegenerative diseases, it should be emphasized to make clear the characteristics of the various types of stem cells. Among stem cells, dental pulp stem cells (DPSCs) are a cell population which is rich in cell proliferation and multipotency. It has been reported that transplanting of DPSCs has protective effects against the model of neurodegenerative diseases. The protective effects are not only differentiated into the target cell type for the disease, but also related to trophic factors released from DPSCs. Recently, it has been reported that serum-free culture supernatant of dental pulp stem cells conditioned medium (DPCM) contains various trophic factors and cytokines, and that DPCM is effective for the model of neurodegenerative diseases such as Alzheimer's disease (AD), Parkinson’s disease (PD), and Amyotrophic Lateral Sclerosis (ALS). Moreover, the use of stem cells from human exfoliated deciduous teeth (SHEDs) has been considered. SHEDs are derived from deciduous teeth that have been disposed as a medical waste. SHEDs have higher differentiation capacity and proliferation ability than DPSCs. In addition, the serum-free culture supernatant of SHEDs (SHED-CM) contains more trophic factors, cytokines, and biometals than DPCM and also promotes neuroprotection. The neuroprotective effect of DPSCs including deciduous teeth will be used as the seeds of therapeutic drugs for neurodegenerative diseases. SHEDs will be used for further cell therapy of neurodegenerative diseases in the future. In this paper, we focused on characteristics and the potential of DPSCs for neurodegenerative diseases.